2001
DOI: 10.1007/s10152-001-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Postsettlement growth of two estuarine crab species, Chasmagnathus granulata and Cyrtograpsus angulatus (Crustacea, Decapoda, Grapsidae): laboratory and field investigations

Abstract: The estuarine grapsid crabs Chasmagnathus granulata and Cyrtograpsus angulatus belong to the most typical and dominant inhabitants of brackish coastal lagoons in southeastern South America. In a combined laboratory and field investigation of juvenile growth, we measured the increase in body size in these species under controlled conditions as well as in field experiments (in Mar Chiquita lagoon, Argentina), seasonal changes in size frequency distribution of a natural population, and growth related changes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
3
20
1
3
Order By: Relevance
“…The distribution of sizes of early staged crabs from natural habitats supports the occurrence of a molt increment around 22% in South Bay tributaries (C. Culver, unpublished data), and is similar to increments reported for small crabs in Germany (24%) (Panning 1939a). This molt increment is similar to growth rates reported for other young juvenile grapsoid crabs (Spivak 1988;Luppi et al 2002) and other decapods (Hartnoll 1982).…”
Section: Juvenilessupporting
confidence: 83%
“…The distribution of sizes of early staged crabs from natural habitats supports the occurrence of a molt increment around 22% in South Bay tributaries (C. Culver, unpublished data), and is similar to increments reported for small crabs in Germany (24%) (Panning 1939a). This molt increment is similar to growth rates reported for other young juvenile grapsoid crabs (Spivak 1988;Luppi et al 2002) and other decapods (Hartnoll 1982).…”
Section: Juvenilessupporting
confidence: 83%
“…Dense populations of this species are found in estuarine mudXats and salt marshes, as well as in coastal bays and lagoons with highly variable salinities, temperatures, and tidal patterns (Spivak 1997). Studies of diVerent populations of this species have shown diVerences, particularly between marine and estuarine habitats, in maximum adult body size, egg size, and in the timing and duration of the reproductive season (see Botto and Irigoyen 1979;D'Incao et al 1992;Anger et al 1994;RuVino et al 1994;Spivak et al 1994Spivak et al , 1996Iribarne et al 1997;Luppi et al 1997Luppi et al , 2002López-Greco and Rodríguez 1999;Ituarte et al 2004;Bas et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Luppi et al [18] compared growth of juvenile N. granulata and Cyrtograpsus angulatus, another grapsoid aquatic euryhaline crab from MC, from megalopae to stage 8 juveniles. Individuals were fed with high protein live diet (Artemia sp.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for size increment per molt, since no differences appeared between diets D and E and similar values were obtained in individuals fed with live Artemia spp. nauplii [18] or Artemia spp. nauplii and frozen Idotea baltica [19].…”
Section: Discussionmentioning
confidence: 99%